Financial Constraints, Investment, and the Value of Cash Holdings - Denis, David J.; Sibilkov, Valeriy (Review of Financial Studies, 2010)
Previous studies report that cash holdings are more valuable for financially constrained firms than for unconstrained firms. We examine (i) why this is so and (ii) why some constrained firms appear to hold too little cash. Our results indicate that greater cash holdings are associated with higher levels of investment for constrained firms with high hedging needs and that the association between investment and value is stronger for constrained firms than for unconstrained firms. These findings imply that higher cash holdings allow constrained firms to undertake value-increasing projects that might otherwise be bypassed. We further find that some constrained firms exhibit low cash holdings because of persistently low cash flows. Overall, our findings support the view that greater cash holdings of constrained firms are a value-increasing response to costly external financing.